2019
DOI: 10.33737/gpps19-tc-091
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Dodge: Avoidance of a Thermoacoustic Instability under Transient Operation

Abstract: Varying one of the governing parameters of a dynamical system may lead to a critical transition, where the new stable state is undesirable. In some cases, there is only a limited range of the bifurcation parameter that corresponds to that unwanted attractor, while the system runs problem-less otherwise. In this study, we present experimental results regarding a thermoacoustic system subject to two consecutive and mirrored supercritical Hopf bifurcations: the system exhibits high amplitude thermoacoustic limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Regarding opportunities for future work, we note that an effect worth exploring is that of the speed with which the forcing conditions are varied. Recent thermoacoustics experiments by Bonciolini & Noiray (2019) have shown that it is possible to dodge a supercritical Hopf bifurcation if the bifurcation parameter can be varied sufficiently quickly. It is thus reasonable to expect an analogous phenomenon occurring in forced synchronization, whereby it may be possible to dodge certain T 2 or T 3 states en route to complete synchronization if f f or f can be varied sufficiently quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding opportunities for future work, we note that an effect worth exploring is that of the speed with which the forcing conditions are varied. Recent thermoacoustics experiments by Bonciolini & Noiray (2019) have shown that it is possible to dodge a supercritical Hopf bifurcation if the bifurcation parameter can be varied sufficiently quickly. It is thus reasonable to expect an analogous phenomenon occurring in forced synchronization, whereby it may be possible to dodge certain T 2 or T 3 states en route to complete synchronization if f f or f can be varied sufficiently quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Bonciolini et al [10] experimentally and numerically verified the tipping-delay phenomenon in rate-dependent thermoacoustic systems driven by Gaussian white noise. Subsequently, they also found that thermoacoustic instabilities can be circumvented when the rate of parameter change is fast enough [11]. Further, Zhang et al [12,13] considered the correlation time of noise, extended the above findings to systems excited by Gaussian colored noise, and obtained the effect of noise correlation time coupled with the rate of parameter change on thermoacoustic systems.…”
Section: Introductionmentioning
confidence: 97%
“…These range from ships experiencing wave induced time varying restoring moments [79], through multiple scale dynamics [9], to investigating the effects of a moving mass on structures [76], or the switching between different working regimes [23], or milling stability with time dependent parameters [17]. Tipping events are sudden changes accompanying parameter drifts, and our method is useful to apply in such cases (see, e.g., [47,72]), too, including the avoidance of instability via fast enough rates of the parameter drift [6,85]. In analogy with climate sensitivity, parameter sensitivity or model uncertainty can be defined in mechanical systems, too (see, e.g., [3,49]), concepts to which the ensemble approach proposed here might be natural to extend.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The nodes become converted into elliptic ones, with eigenvalues ±i √ 2. These snapshot elliptic points (SEPs) are, from (6), given by:…”
Section: Snapshot Hyperbolic and Elliptic Pointsmentioning
confidence: 99%
See 1 more Smart Citation